2017
DOI: 10.1007/s11307-017-1048-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Bevacizumab Therapy Effect on Colon Cancer Subtypes by Using Whole Body Imaging in Mice

Abstract: Our data suggest that SW480 and SW620 cell lines respond differently to Bevacizumab therapy in vivo. Because of higher vascularization, and subsequently higher reduction by drug of new blood vessels and tumor growth rate, xenografts derived from the metastatic SW620 cell line have a better chance of being successfully treated with Bevacizumab compared with those derived from the primary tumor SW480 cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Viability of HCEC-1CT cells was significantly dose-dependently reduced under bevacizumab and FOX/bevacizumab treatments, while only the highest tested concentration of bevacizumab in combination with FOX was able to significantly reduce the viability of SW620. In contrast to our results, Vuletic et al showed that 25 and 50 µg/ml bevacizumab decreased significantly SW620 cell viability to approximately 90%, whereas we were unable to observe citotoxic effects even under 250 µg/ml bevacizumab [57] l bevacizumab had slightly increased proliferation of SW620, however, these cells were grown in hypoxic (1% O 2 ) and serum-reduced (1% FBS) conditions [58]. Overall, HCEC-1CT cells were more sensitive to the tested drugs in comparison to the SW620 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Viability of HCEC-1CT cells was significantly dose-dependently reduced under bevacizumab and FOX/bevacizumab treatments, while only the highest tested concentration of bevacizumab in combination with FOX was able to significantly reduce the viability of SW620. In contrast to our results, Vuletic et al showed that 25 and 50 µg/ml bevacizumab decreased significantly SW620 cell viability to approximately 90%, whereas we were unable to observe citotoxic effects even under 250 µg/ml bevacizumab [57] l bevacizumab had slightly increased proliferation of SW620, however, these cells were grown in hypoxic (1% O 2 ) and serum-reduced (1% FBS) conditions [58]. Overall, HCEC-1CT cells were more sensitive to the tested drugs in comparison to the SW620 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…The applied techniques of small animal fluorescence molecular imaging have been widely used in the monitoring of therapy effects ( Vuletic et al, 2017 ) or enzyme activity ( Bremer et al, 2005 ) and in the investigation of distribution patterns of novel therapeutics, e.g. nanomedicines ( Kunjachan et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…target is not clear, but tumor cells are able to internalize activated integrins (Guo and Giancotti, 2004;Nieberler et al, 2017), therefore paving the way for an accumulation of probes inside target cells. The applied techniques of small animal fluorescence molecular imaging have been widely used in the monitoring of therapy effects (Vuletic et al, 2017) or enzyme activity (Bremer et al, 2005) and in the investigation of distribution patterns of novel therapeutics, e.g. nanomedicines (Kunjachan et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…[3] In 2004, bevacizumab, a humanized full-length immunoglobulin G against VEGF, was approved by the US Federal Drug Administration for the management of colon cancer. [4] Bevacizumab is now being used as an "off-label" intravitreal agent for wet age-related macular degeneration (AMD), diabetic retinopathy, and retinal vein occlusions globally. [5] Intravitreal injections of ranibizumab and aflibercept are both approved for wet-type AMD and macular edema due to retinal vascular disorders.…”
Section: Vascular Endothelial Growth Factor (Vegf) Plays a Substantial Role In Angiogenesis Andmentioning
confidence: 99%